Impact of mobile Internet use on health-seeking behaviors: evidence from China - Lin, ChenLei; Lin, Hong (Frontiers in Public Health, 2024)
Introduction: Although health-seeking behaviors are crucial to China's healthcare delivery system, the influence of mobile Internet use in this context remains under-explored. This study aimed to comprehensively explore the influence of mobile Internet use on health-seeking behaviors, and meticulously examined the heterogeneity in health outcomes associated with the intersection between mobile Internet use and health-seeking behaviors. Methods: We used nationally representative data derived from the China Family Panel Studies. Given that individuals typically make the decision to use mobile Internet autonomously, an instrumental variable regression methodology was adopted to mitigate potential selection biases. Results: Our findings revealed that mobile Internet use significantly promoted self-medication and adversely affected the use of primary care facilities among Chinese adults. Furthermore, our findings highlighted the heterogeneous effects of mobile Internet use across diverse health demographic groups. Conclusions: These findings underscore the importance of strategic planning and utilizing mobile Internet resources to steer individuals toward more appropriate healthcare-seeking behaviors.According to Billari et al. ( 1), a new era in the digital revolution is emerging. Moreover, information and communication technologies (ICTs) are at the forefront of significant transformations in the distribution and accessibility of health and medical information. Fox and Duggan (2) reported that many Internet users actively seek health information online. This transition facilitates individuals in acquiring knowledge regarding their health, addressing health challenges, making informed health decisions, and adopting behavioral changes (3,4), which has significantly narrowed the knowledge and power gap between healthcare professionals and the general populace (5). A nationwide survey by Wang et al. (6) revealed that approximately 33.2% of Chinese adults actively sought health information via the Internet. Following the outbreak of COVID-19, the "China Internet Development Report 2022" revealed that, as of December 2022, the number of users participating in health-related Internet activities in China had increased to 363 million, accounting for 34% of the total Chinese